Tindak Pidana Perzinahan dalam Persfektif Hadis - Dol, Sri Karmila; Hafid, Arwin; Rasyid, Muhammad Dirman; Reskiani, Anugrah (STAIN Majene, 2025)
Abstract: This paper discusses adultery as a criminal offense in Islam based on the Prophetic traditions. It aims to explore the concept of zina, the sanctions imposed on perpetrators, and the relevance of applying Islamic criminal law in contemporary social contexts. Using a normative-theological approach and qualitative descriptive methods, the data are obtained from primary sources in the form of authentic hadiths and supported by secondary literature. The study reveals that Islam imposes firm sanctions against adultery, such as stoning for married offenders (muḥṣan) and flogging for unmarried ones (gairu muḥṣan), serving both as a preventive and educational measure to uphold public morality. In Indonesia, its application faces legal challenges, as adultery is classified as a complaint-based offense. This study recommends a reformulation of national criminal policies grounded in hadith values to realize a fair and moral legal system. Abstrak: Tulisan ini membahas perzinaan sebagai salah satu bentuk tindak pidana dalam Islam berdasarkan hadis-hadis Nabi Muhammad SAW. Penelitian ini bertujuan untuk menggali secara mendalam konsep zina, sanksi terhadap pelakunya, serta relevansi penerapan hukum zina dalam konteks sosial kontemporer. Menggunakan pendekatan normatif-teologis dan metode kualitatif deskriptif, data diperoleh dari literatur primer berupa hadis-hadis ṣaḥīḥ serta literatur sekunder pendukung lainnya. Hasil kajian menunjukkan bahwa Islam menetapkan sanksi tegas terhadap zina, seperti rajam bagi pelaku yang telah menikah (muḥṣan) dan cambuk bagi yang belum menikah (gairu muḥṣan), sebagai upaya preventif dan edukatif dalam menjaga moralitas publik. Dalam konteks Indonesia, penerapan hukum ini dihadapkan pada sistem hukum nasional yang menetapkan zina sebagai delik aduan. Kajian ini merekomendasikan reformulasi kebijakan hukum pidana nasional berbasis nilai-nilai hadis, demi mewujudkan sistem hukum yang adil dan bermoral.